EXPLORING THE IMPACT OF BABY MASSAGE ON SLEEP QUALITY: A STUDY AT PRATAMA AULIA MEDIKA CLINIC, CIREBON REGENCY - Adisti, Putri Nawal; Hidayah, Fika Nur; Nurfita, Nisa Rizki (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Sleep is an important adaptation process for babies as they adjust to their environment. According to 2018 World Health Organisation (WHO) data published in the journal Pediatrics, around 40% of infants experience sleep problems. One potential intervention to address this is infant massage. This study aims to explore the characteristics of infants, assess the quality of infant sleep before and after receiving massage, and evaluate the effect of infant massage on infant sleep quality at Klinik Pratama Aulia Medika Girinata. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 infants aged 0-12 months who were selected using purposive sampling. Data were analysed using univariate and bivariate analyses, with Wilcoxon test used for statistical evaluation. The results showed that before receiving infant massage, most infants (n=13.52%) were categorised as having poor sleep quality. In contrast, after the massage intervention, most infants (n= 14.56%) were classified as having good sleep quality. The Wilcoxon statistical test yielded a significant p-value of 0.000, which is smaller than the alpha level of 0.05, thus supporting the acceptance of the alternative hypothesis (Ha). The findings suggest infant massage has a positive influence on improving the sleep quality of infants aged 0-12 months at Pratama Aulia.